PROBLEMATIC ISSUES OF HIGHLY ACTIVE ANTIRETROVIRAL THERAPY IN HIV-INFECTED PATIENTS WITH ENDOGENOUS MENTAL DISORDERS - N. G. Neznanov; N. B. Khalezova; A. A. Khobeish; N. P Petrov (Журнал инфектологии)
The aim: to identify changes in mental status due to receive HAART and comprehensive assessment of the biological, behavioral and social factors in adherence to treatment in HIV-infected patients with endogenous mental disorders. Material: The study involved 53 patients with HIV infection and schizophrenia / affective spectrum comorbidity. Results: In the tolerability and adherence to ARV therapy affects not only the neurobiological vulnerability, but also a change in the mental state and condition of the patient social life. After the start of ART mental state of patients with endogenous mental disorders often deteriorates. Depending on their degree of penetration into the central nervous system were observed pronounced effect of ART on the structure of psychopathological symptoms and the course of mental illness in general.